Experimental Study and Evaluation of Mechanical Properties of Nano-Scale Single and Composite Structures (PCL/PU) Fabricated by Co-Electrospinning and Blend-Electrospinning Methods. - Nafiseh Jirofti; Davod Mohebbi-Kalhori; Afra Hadjizadeh; Gholam Hosein Kazemzadeh; Reza Taheri (Fasa University of Medical Sciences, 2019)
Background & Objective: Extracellular matrix (ECM) as a three-dimensional structure consisting of protein nanofibers and polysaccharides with a diameter of 50-500 nm is a place to store cells. Electrospinning is a method that allows nanofibers to be produced in this range and even beyond. Materials & Methods: Polycaprolactone, polyurethane, and required solvents chloroform, ethanol, Tetrahydrofuran, dimethylformamid and 1,1,1,3,3,3-Hexafluoro-2-propanol were used without any purification. Single and composite scaffolds were fabricated of these polymers using Co-electrospinning and Blend-electrospinning methods. The morphological and mechanical properties of the neat and composite structures were evaluated through SEM, FTIR, and Tensile tese. Result: Results showed that the average fiber diameter and Young's modulus changes' range in composite and single structures obtained 228 ± 89 to 470 ± 95 nm and 1.2 ± 0.39 to 8.03 ± 0.54 MPa. Composite structures fabricated using Co-electrospinning method have smaller mean fiber diameter 228 ± 89 nm and composite structures fabricated using blend electrospinning have highest Young's modulus 8.03 ± 0.54 MPa comparison single structures.  Conclusion: The results showed that the produced composite structure meets the required mechanical properties to be used in tissue engineering and, because of its structural and morphological features, can be also applied as alternative scaffolds in the body. Composite structures produced by blend electrospinning method show a higher degree of strength compared to similar composite structures that produced by co-electrospinning method due to the free movement of the polyurethane nanofiber and the intrinsic contraction in the composite structure.